PERAN PEREMPUAN DALAM POLITIK DI INDONESIA - Fahmi Ali Ramdhani (Universitas Islam Nusantara, 2021)
Women's political rights are fundamentally human rights, and human rights are the essence of the democratic framework. Therefore, involving women and men in the decision-making process is an absolute requirement in democracy. In this theory, in fact, there is no longer a female-male dichotomy. But in reality women's rights are still being politicized and mobilized in the name of democracy. With the fulfillment of the 30% quota for women's representation in parliament, there are at least two symptoms that can result from this excess. First, there is the seriousness of women in trying to enter the world of politics. In addition, politics is a state policy that regulates the direction and goals of the state, so that the policy-making process can be carried out by all components of the nation, including women. Second, public awareness to provide opportunities for women not only to vote but also to be elected.Hak politik perempuan pada dasarnya adalah hak asasi manusia, dan hak asasi manusia merupakan esensi dari kerangka demokrasi. Oleh karena itu, melibatkan perempuan dan laki-laki didalam proses pengambilan keputusan menjadi syarat mutlak dalam demokrasi. Dalam teori ini sesungguhnya tidak lagi ada dikotomi perempuan-pria. Tapi pada kenyataannya hak perempuan masih dipolitisasi dan dimobilisasi atas nama demokrasi. Dengan terpenuhinya quota 30 % keterwakilan perempuan diparlemen minimal ada dua gejala yang dapat ditimbulkan dari ekses tersebut. Pertama, adanya kesungguhan perempuan untuk berupaya mau terjun kedunia politik. Selain itu, kesadaran perempuan itu sendiri bahwa politik adalah bidang kebijakan kenegaraan yang mengatur arah dan tujuan negara, sehingga proses pengambilan kebijakan dapat dilakukan secara politis oleh semua komponen bangsa termasuk perempuan. Kedua, kesadaran masyarakat untuk memberikan kesempatan kepada perempuan untuk tidak saja memilih tetapi juga dipilih.